2013
DOI: 10.1080/02568543.2012.739987
|View full text |Cite
|
Sign up to set email alerts
|

Aggression Levels of 5- to 6-Year-Old Turkish Children in Terms of Gender, Age, and Peer Relations Variables

Abstract: The purpose of this study is to assess the aggression levels of 5-to 6-year-old Turkish children in terms of various variables. Participants of this study were 697 children (335 girls and 362 boys) attending preschool. According to study results, the level of aggression in Turkish children between ages 5 and 6 changed, based on all variables in the research. The variables used to determine children's levels of aggression were gender, age, prosocial behavior, asocial behavior, exclusion, fearful-anxiety, hypera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 56 publications
1
4
0
1
Order By: Relevance
“…Clear gender differences have also been revealed. Boys were more likely to be involved in physical fights (Alikasifoğlu et al, 2004), display both proactive and reactive aggressive behaviours (Gülay Ogelman, 2013;Uz Baş & Topçu Kabasakal, 2010;Uz Baş & Yurdabakan, 2012), and be victimized than girls (Doğan Ateş & Yağmurlu, 2010). Most of these available studies pertain to physically aggressive behaviours during elementary or middle-school in Turkey.…”
Section: Childhood Physical Aggression In Turkeymentioning
confidence: 99%
See 1 more Smart Citation
“…Clear gender differences have also been revealed. Boys were more likely to be involved in physical fights (Alikasifoğlu et al, 2004), display both proactive and reactive aggressive behaviours (Gülay Ogelman, 2013;Uz Baş & Topçu Kabasakal, 2010;Uz Baş & Yurdabakan, 2012), and be victimized than girls (Doğan Ateş & Yağmurlu, 2010). Most of these available studies pertain to physically aggressive behaviours during elementary or middle-school in Turkey.…”
Section: Childhood Physical Aggression In Turkeymentioning
confidence: 99%
“…Despite studies showing the negative outcomes associated with proactive and reactive physical aggression, there is still a limited understanding of parents' feelings and views about these two functions of physical aggression and the strategies they use to intervene with such child transgressions during early childhood. This information is especially lacking in societies such as Turkey, where physical aggression has more recently been identified as a widespread problem in schools (e.g., Alikasifoğlu et al, ; Doğan Ateş & Yağmurlu, ; Gülay Ogelman, ). Knowledge about parents' emotions, cognitions, and approaches to different types of physical aggression in the preschool years is crucial because parents take an essential socializing role (Edwards & Liu ) and show intensive and heightened efforts during this developmental period (Olson et al, ).…”
Section: Parenting Beliefs and Behaviours In The Turkish Cultural Conmentioning
confidence: 99%
“…According to our study, boys are significantly more aggressive and less shy than girls. In a study conducted with Turkish preschool children, boys are again found to be significantly more aggressive than girls (Gülay-Ogelman, 2013). When different types of aggression is examined, it is found that physical aggression is usually more common among males than females (Juliano, Werner, & Cassidy, 2006;Kuperschmidt, Bryant, & Willoughby, 2000) however relational aggression studies show confusing results.…”
Section: Discussionmentioning
confidence: 99%
“…According to Eagly and Steffen's early study (1986) male gender role is defined by several forms of aggression. Authors who have investigated the male gender role have reported that that males are expected to be rough, dominant, strong and aggressive However, girls are accepted by their so-called cute and quiet status (Gülay-Ogelman, 2013). Similarly shyness is less tolerable for boys than for girls because it disrupts gender rules in terms of the expected male roles like social assertion and domination (Rubin, Coplan, & Bowker, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Çalışmanın diğer boyutu olan akran şiddeti ile ilişkili faktörler incelendiğinde erkek çocukların kızlara oranla hem akran şiddetine maruz kalma hem de akran şiddeti uygulama puan ortalamalarının daha yüksek olduğu bulunmuştur. Literatürde cinsiyetin akran şiddetini etkileyen önemli bir etmen olduğu ve bu çalışmayla uyumlu olarak erkeklerin kızlardan daha fazla akran şiddetine maruz kaldığı ve şiddet uyguladığı belirtilmektedir (3,35,36). Bu farklılığın erkek çocukların kız çocuklara oranla daha hareketli olmaları, fiziksel güçlerinin daha fazla olması, toplumun erkek çocuklarına yüklediği cinsiyet rolü ve erkeklerin saldırgan davranışlarının pekiştirilmesi ile ilgili olduğu söylenebilir.…”
Section: Discussionunclassified